ANALISA EXERGI SISTEM PEMBANGKIT UAP PILOT PLANT BIODIESEL - Ambo Intang (Universitas Sultan Ageng Tirtayasa, 2015)
The Efforts to reduce the use of fossil fuels is to innovate in order to support the equipment more efficient in the use of fuel and the use of alternative energy sources to power generation. In the biodiesel pilot plant, each of these can be done at once by doing exergy analysis on the energy conversion process components, in this case, especially on the part of the combustion chamber and heat exchanger. The results of this study indnicate that the room is toasty exergy destruction is still above 30% (B0: 66.29%; B20: B50 and 54.38%: 56.13%) this allows for improved space efficiency boiler to burn to prevent the destruction exergy such high. Exergy destruction in the heat exchanger has taken 30% (B0: 29.17%; B20: B50 and 24.78%: 24.12%). Percentage exergy destruction in the combustion chamber of the lowest in the B20 and B50 increased, meaning the addition of biodiesel in diesel fuel to improve the level of energy and the increasing quality of biodiesel in the fuel mix will again lower the level of quality of energy.